Phase 2, randomized, open‐label study of ramucirumab in combination with first‐line pemetrexed and platinum chemotherapy in patients with nonsquamous, advanced/metastatic non–small cell lung cancer. Issue 6 (6th November 2014) - Doebele, Robert C.; Spigel, David; Tehfe, Mustapha; Thomas, Sachdev; Reck, Martin; Verma, Sunil; Eakle, Janice; Bustin, Frederique; Goldschmidt, Jerome; Cao, Dachuang; Alexandris, Ekaterine; Yurasov, Sergey; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Vascular endothelial growth factor (VEGF)–mediated angiogenesis plays an important role in non–small cell lung cancer (NSCLC). Ramucirumab is a human immunoglobulin G1 monoclonal antibody that inhibits VEGF receptor 2. This phase 2 study investigated ramucirumab in combination with first‐line pemetrexed and platinum chemotherapy in advanced/metastatic NSCLC. METHODS Eligible stage IV nonsquamous NSCLC patients with no prior chemotherapy for metastatic disease were randomized 1:1 to pemetrexed and carboplatin (or cisplatin) or ramucirumab (10 mg/kg) plus pemetrexed and carboplatin (or cisplatin) once every 3 weeks. Treatment was given for 4 to 6 cycles, and this was followed by a maintenance phase with pemetrexed or ramucirumab and pemetrexed. The primary endpoint was progression‐free survival (PFS) with a sample size of sufficient power to detect an increase from 7 to 10.4 months. RESULTS From October 2010 to October 2011, 140 patients were randomized (pemetrexed‐platinum arm, 71; ramucirumab‐pemetrexed‐platinum arm, 69), and most baseline characteristics were similar for the 2 treatment arms. The median PFS was 5.6 months for the pemetrexed‐platinum arm and 7.2 months for the ramucirumab‐pemetrexed‐platinum arm (hazard ratio, 0.75; P = .132). The objective response rates were 38.0% and 49.3% for the pemetrexed‐platinum and ramucirumab‐pemetrexed‐platinum arms, respectively (P = .180). The disease control rate was 70.4% for the pemetrexed‐platinum arm and 85.5% for the ramucirumab‐pemetrexed‐platinum arm (P = .032). The grade 3 or higher adverse events occurring in 10% or more of patients were thrombocytopenia, neutropenia, fatigue, anemia, nausea, back pain, and hypertension. CONCLUSIONS The primary endpoint of significant prolongation of PFS was not met; however, ramucirumab showed evidence of clinical activity in combination with pemetrexed and platinum in nonsquamous NSCLC patients. The addition of ramucirumab to pemetrexed and platinum did not result in new or unexpected safety findings. Cancer 2015;121:883–892. © 2014 American Cancer Society.